KEPUASAN KERJA DAN KINERJA PERSONIL POLDA ACEH - Supriadi Supriadi; Nasir Nasir; M Shabri Abd Majid (FEB - Unsyiah, 2018)
The purpose of this research is to know: (1) description of leadership, career development, personnel work satisfaction and performance of Aceh Police, (2) the influence of leadership on job satisfaction of personnel, (3) the influence of career development on job satisfaction of personnel, (4) the effect of performance allowances on employee job satisfaction, (5) the influence of leadership on the performance of personnel, (6) the influence of career development on the performance of personnel, (7) the effect of performance allowances on the performance of the Aceh Police, (8) the effect of job satisfaction on personnel performance of Aceh Police personnel, (9) the influence of leadership, career development and performance benefits on the performance of Aceh Police personnel through job satisfaction of Aceh Police personnel. This research was conducted at Polda Aceh. As for the object of this research is leadership, career development and performance benefits, job satisfaction, personnel performance. The results show that leadership, career development, performance benefits, personnel job satisfaction and performance of Aceh Police personnel have been running well. Leadership has a significant effect on employee job satisfaction, Performance allowance has a significant effect on employee job satisfaction, Leadership has a significant effect on the performance of Aceh Police personnel, Career development has a significant effect on the performance of Aceh Police personnel, Performance allowance has a significant effect on performance of personnel of Polda Aceh, Satisfaction of personnel work have significant influence to performance of Polda Aceh personnel, There is indirect influence of leadership, career development and performance allowance to job satisfaction of Polda Aceh personnel through job satisfaction of personnel